Rural livelihoods, forest products and poverty alleviation: the role of markets - Mutamba, Manyewu (Rhodes University, Faculty of Science, Department of Environmental Science, 2013)
There is growing acknowledgement that forests and forest products are central to rural livelihoods, but their role in lifting households out of poverty remains contentious. This study tested the assertion by proponents of forest based poverty alleviation that changing conditions in the use and management of forests and forest products has created opportunities for poor rural households to lift themselves out of poverty. The study used detailed annual income data from various household sectors in two contrasting sites in Zambia, namely Mufulira and Kabompo districts, analyzing the relative contribution of forest income to household livelihood, the effect of household wealth status on forest use, factors driving household participation in forest product trade, and the influence of distance to urban markets on trends in the use of forest products. The study found that forest based activities play a central role in the livelihoods of households in the two study sites, contributing close to half of total household income, and dwarfing the contribution of agricultural sectors such as cropping and livestock rearing which are generally regarded as the main income sources for rural households. Forest based sectors were also found to be particularly valuable sources of household cash, often coming at critical times to meet basic needs. The findings also revealed that without the contribution of forest income, the proportion of households that would fall below the poverty line would increase sharply in both study sites. Wealthier households earned higher magnitudes of both subsistence and cash income from forest based activities than their poorer counterparts. Even the share of total household income coming from forest based activities was also higher among these better-off households, confirming that these activities are lucrative and they are improving the wealth status of households. Household participation in forest product trade was found to be influenced by demographic factors such as number of productive household members, age and the education level of the household head. Economic factors such as the level of income from wage labour, household poverty level, and ownership of key assets such as a bicycle were found to be important. Distance of homestead from the forest was also found to be an important contextual variable. The influence of urban demand on the use of forest products by rural households was significant in the study area. Although local sales played an important part as a source of cash for households, the most preferred channels for trade were linked to urban markets, either through roadside markets, middlemen or direct sales to urban buyers. The study concluded that with improved local organization and support for product development and marketing, some forest based activities provide a viable poverty alleviation option for poor rural households who otherwise have limited economic opportunities to escape poverty.
Keywords: Rural development -- Zambia; Rural poor -- Zambia; Zambia -- Rural conditions; Forest management -- Zambia; Forest conservation -- Zambia; Households -- Economic aspects -- Zambia; Forest products -- Zambia; Forests and forestry -- Zambia; Non-timber forest products -- Zambia